Cold spraying SiC/Al metal matrix composites: effects of SiC contents and heat treatment on microstructure, thermophysical and flexural properties. (23rd February 2018) - Gyansah, L; Tariq, N H; Tang, J R; Qiu, X; Feng, B; Huang, J; Du, H; Wang, J Q; Xiong, T Y
Abstract: In this paper, cold spray was used as an additive manufacturing method to fabricate 5 mm thick SiC/Al metal matrix composites with various SiC contents. The effects of SiC contents and heat treatment on the microstructure, thermophysical and flexural properties were investigated. Additionally, the composites were characterized for retention of SiC particulates, splat size, surface roughness and the progressive understanding of strengthening, toughening and cracking mechanisms. Mechanical properties were investigated via three-point bending test, thermophysical analysis, and hardness test. In the as-sprayed state, flexural strength increased from 95.3 MPa to 133.5 MPa, an appreciation of 40% as the SiC contents increased, and the main toughening and strengthening mechanisms were zigzag crack propagation and high retention of SiC particulates respectively. In the heat treatment conditions, flexural strength appreciated significantly compared to the as-sprayed condition and this was as a result of coarsening of pure Al splat. Crack branching, crack deflection and interface delamination were considered as the main toughening mechanisms at the heat treatment conditions. Experimental results were consistent with the measured CTE, hardness, porosity and flexural modulus.